Impact of roasting levels and brewing cycles on bioactive compounds in spent coffee grounds - Nur Maiyah; Soraya Kerdpiboon; William L. Kerr; Wanwimol Klaypradit; Chayada Smithisukul; Suriyan Supapvanich (Food Chemistry X, 2026)
Spent coffee grounds (SCGs) represent a potential source of residual bioactive compounds for sustainable reuse. Effects of roasting levels and sequential brewing cycles on recovery of total phenolic content (TPC), total flavonoid content (TFC), caffeine, and chlorogenic acid (CGA) from Arabica and Robusta SCGs were investigated. Coffee beans were roasted (light, medium, dark), brewed through three hydrothermal cycles, and the resulting SCGs extracted with 70% ethanol. The first brewing cycle removed most water-soluble bioactive compounds, while subsequent brews induced smaller compositional changes, indicating the persistence of functional compounds. Roasting influenced the initial bioactive profile, but its impact diminished after brewing. Robusta SCGs retained higher TPC and antioxidant activity while caffeine diminished with brewing cycle, they were relatively stable to roasting while CGA was more heat-sensitive. Principal component analysis confirmed brewing history as the main factor governing SCG chemical profiles. These findings support brewing-informed SCG valorization for sustainable functional food applications.
Keywords: Coffee research and impacts; Tea Polyphenols and Effects; Global trade, sustainability, and social impact